PENGARUH HASIL PEMERIKSAAN PEMERINTAH TERHADAP TINGKAT KORUPSI DAERAH DI JAWA TENGAH (Studi Empiris pada Pemerintah Kabupaten dan Kota di Jawa Tengah Tahun 2017-2022) - Baldan, Kholil; Haryanto, Haryanto (Diponegoro Journal of Accounting, 2024)
This study investigates the impact of governmental audit results on regional corruption levels in Central Java from 2017 to 2022, focusing on audit opinion, findings, and rectification follow-up as independent variables. This research used purposive sampling and resulted 184 total samples of regencies and cities in Central Java over six years. Using multiple linear regression analysis via SPSS 26, secondary data from Indonesian Audit Board (BPK), High Prosecutor's Office (Kejaksaan Tinggi), and Central Bureau of Statistics were analyzed. Results indicate that audit rectification follow-up has a significant negative effect on the corruption levels, while audit opinion and audit findings show no significant influence. However, these factors affect the corruption levels collectively.